The Effect of Dhikrullah on Brain Health According to Neuroscience - Iskandar Iskandar; M. Dirhamsyah (Asian Social Work Journal, 2019)
Dhikrullah according to verse 2 of chapter al-Anfal and verse 28 of chapter ar-Rad in the Koran has a vibrational effect on the calmness of the heart. Dhikrullah has been practiced by Muslims for more than a thousand years, but the explanation of the implications of the dhikrullah's vibration on human health from the neuroscience approach has yet to be completed. This study is an academic response to get scientific answers about the influence of dhikrullah on the health of the human brain. The attention of Islamic scholars to dhikrullah phenomena from the scientific approach is still far from hope, so the explanation of the effects of the dhikrullah's vibration on human mental health has not been completed. In this study, the authors used combined data, qualitative data from 4 respondents to find the model of dhikrullah and quantitative data from 10 subjects to obtain samples of brain waves through Electro Encephalo Graf (EEG) to see the effects of the dhikrullah on human brain waves. The results of the study show that the brain tends to adjust its frequency with the frequency of the sound stimulus it receives through the ear. Dhikrullah's vibration influences beta waves and alpha waves on the subject's brain waves while running the dhikrullah. According to EEG, dhikrullah is proven to be able to present alpha waves as a stimulus to neurotransmitters in the human brain to produce endorphins. Therefore, the authors conclude that this study is a new approach to see the process of the significance of the dhikrullah's vibration on human health. The United Nations, especially WHO, can use dhikrullah vibration as an approach to help human beings who need a solution from a spiritual approach permanently.